1995
DOI: 10.1136/bjo.79.8.719
|View full text |Cite
|
Sign up to set email alerts
|

How effective is an integrated approach to low vision rehabilitation? Two year follow up results from south Devon.

Abstract: Aims-A survey was undertaken to assess the effectiveness of an integrated approach to the provision of low visual aids (LVAs) in south Devon over a 2 year follow up period. This integrated approach includes the assessment of patient needs by low vision therapists, followed by the provision of suitable LVAs, with particular emphasis on training in their use.Methods-A total of 125 patients were selected at random from the 445 patients seen in the low vision clinic at Torbay Hospital in the year 1991. These patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
41
3
6

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 7 publications
6
41
3
6
Order By: Relevance
“…8 To examine the association between training and treatment success, Shuttleworth et al administered the patient satisfaction questionnaire used by McIlwaine et al to the patients at a low vision clinic in which training was an integral part of the service. 4,13 In total, 92% of patients reported that the service was sufficient to meet their needs, which is higher than the 55% of patients in the original survey study. 13 As Nilsson and Nilsson reported, improvement in distance and near visual acuity obtained with aids cannot be translated directly into improvements in visual performance in daily life; training is necessary.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…8 To examine the association between training and treatment success, Shuttleworth et al administered the patient satisfaction questionnaire used by McIlwaine et al to the patients at a low vision clinic in which training was an integral part of the service. 4,13 In total, 92% of patients reported that the service was sufficient to meet their needs, which is higher than the 55% of patients in the original survey study. 13 As Nilsson and Nilsson reported, improvement in distance and near visual acuity obtained with aids cannot be translated directly into improvements in visual performance in daily life; training is necessary.…”
Section: Discussionmentioning
confidence: 60%
“…4,13 In total, 92% of patients reported that the service was sufficient to meet their needs, which is higher than the 55% of patients in the original survey study. 13 As Nilsson and Nilsson reported, improvement in distance and near visual acuity obtained with aids cannot be translated directly into improvements in visual performance in daily life; training is necessary. 10 We think that low vision clinics must provide training, and motivate patients to use LVAs, which requires additional time and skilled staff.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Early studies tended to judge the outcomes of a service by either evaluating the frequency of use of low vision aids by patients at follow-up of a variable period 103,131,150 or by assessing clinical measures of visual function, such as visual acuity or reading speed. 69,93,100,107 Although clinical outcomes are important, they do not necessarily reflect the abilities that the patients will show in their home environment; for example, a large discrepancy has been demonstrated between individuals with a good near VA in the clinic (75%), and those able to resolve small print at home (39%).…”
Section: Outcome Measures For Assessing the Effectiveness Of A Sermentioning
confidence: 99%
“…Registration as blind or partially sighted, for all its defects does trigger some support. Local and national organisations for visually impaired people have an important role and have initiated the development of multiprofessional integrated services 36. These organisation often provide low vision aids to help with many daily tasks, including reading.…”
Section: Visual Impairmentmentioning
confidence: 99%